Experimental observations of local geological structures of the Pobuz’kyi mining region (Zavallya) using the MTZ and MVP methods - Ilyenko, V.A.; Burakhovich, T.K.; Kushnir, A.M.; Shyrkov, B.I. (Reports of the National Academy of Sciences of Ukraine, 2020)
The article presents the results of experimental observations of a lowfrequency natural alternating electromagnetic field of the Earth of the external ionosphericmagnetospheric origin, conducted in 2019, on the territory of the Zavallya ore field of the Pobuz’kyi mining district of the Ukrainian Shield. After applying the procedures of synchronous estimation of MT/MV transmitting operators using the PRC_MTMV software complex, the complex induction parameters for periods from 60 to 4000 s and amplitude curves of the resistivity and impedance phases for a wide range of periods from 10 to 10000 s were obtained. A qualitative analysis of the experimental parameters showed that local geological structures are characterized by a very complex structure in geoelectric terms. On the one hand, this is the presence of surface and nearsurface local threedimensionality, as indicated by the tiper behavior and the low values of the curves Pp in the vast majority of observation points. On the other hand, it is a sharp change in the tellurium currents, which can be caused by the presence of local threedimensional surface inhomogeneities caused by the particular composition of rocks and by the intersection zones of a large number of multifaceted geological faults associated with the intense crushing of rocks. Some behavior of the curves of the apparent resistivity may be justified by the influence of closely spaced regional conductive deeplocation structures. It should be said that the main type of high electrical conductivity over the area of the Zavallya ore field may be the electronic one, which is associated with the graphitization of large volumes of rocks of the granite layer and the high connectivity. The nature of the electrical conductivity of such regions can be explained by various causes ranging from the peculiar formation of conductive inclusions in the grain space to the anisotropy of fracture and the stratification of rocks.